Government Debts and Economic Growth: The Case for Selected EU Countries - Kum, Hakan; Oktem, Ozlem (International Journal of Economics and Financial Issues, 2018)
This study examines the relationship between economic growth and government debt for 15 European Union countries (Austria, Belgium, Finland, France, Germany, Greece, Ireland, Italy, Luxembourg, the Netherlands, Portugal, Slovakia, Spain, Estonia, Slovenia) between 2000-2016. We have used the GDP, GFC, labor, and OECD data which we have obtained from the World Bank database. The econometric method used in this study was ARDL Panel Mean Group (PMG). According to the findings obtained from the study, the increase in GDP caused a decrease in government debt in the short term and increased the government debt in the long term. Keywords: Government Debt, Economic Growth, Panel Analysis, European Union (EU) JEL Classifications: H63, C33, C23 DOI: https://doi.org/10.32479/ijefi.7399